PP.07.06: ROLE OF AMBULATORY BLOOD PRESSURE MONITORING ASSESSMENT REPLACEMENT THERAPY OF HYPOCORTICISM IN ALLGROVE SYNDROME. (June 2015) - Lalic, T.; Stojanovic, M.; Ciric, J.; Beleslin, B.; Savic, S.; Stojkovic, M.; Nisic, T.; Barac, M.; Zarkovic, M.
Abstract : Objective: Allgrove (Triple A) syndrome is a rare autosomal recessive hereditary disorder that is characterized by: adrenocorticotropic hormone (ACTH) resistant Adrenal insufficiency (AI), Achalasia and Alacrimia, autonomus symptoms and neurodegeneration. A typical phenotype consisting of short stature, microcephaly, small spastic tongue with atrophy of the papillae, osteoporosis and pes kavus. Responsible AAAS gene on 12q13. Described about a hundred cases so far. Design and method: To illustrate the two cases of a rare hereditary syndrome and ABPM importance in assessing replacement therapy. Results: The first patient, 21 year old boy, at the age of five achalasia cardia determined and committed cardiomiothomy. Then set up and alacrimia. Problems with walking and progression of neurological symptoms. At the age of 11 AI diagnosed and set the clinical diagnosis of Allgrove sy. Introduced hydrocortisone. Occasionally, difficulty swallowing, weakness, fatigue, expressed excavatus feet, lower TA and bradycardia.The younger brother, 13 years old, also has Allgrove sy. Short stature, gracile and characteristic stigmata at examination, normal findings on heart and lungs, TA 125/75 mmHg, pulse 86/min. No orthostatic hypotension. ABPM at Hydrocortison 10 + 5 + 5 mg (7 h, 16 h, 22 h) showed normal systolic and diastolic blood pressure during the day and night. Diastolic blood pressure during the day were at the upper limit. Day 127/86 mmHg Night 108/64 mmHg. Second patient, 39 years old man, at age of 21 AI diagnosed and hydrocortisone introduced. In 2003 achalasia and diverticulum of the esophagus diagnosed after which he underwent surgery. He lacks of strenth for heavy physical labor sometimes. Normally fed, dark skin and scar from the surgery. The normal respiratory sound. Telesystolic ejection murmur 1/6 above the tup, TA 120/70 mmHg, pulse 70/min. ABPM at Hydrocortison 10 + 5 + 5 mg (8 h, 13 h, 17 h) showed lower systolic and diastolic blood pressure during the day and night. The values were lower during the night compared to daytime. Advised to add fludrocortisone. Conclusions: ABPM could be very important for assessing the adequacy of replacement therapy of hypocorticism especially when accompanied with another problems and conditions.